MOTHER EARTH AND NEW AGE SPIRITUALITY - Scott, David C. (Journal of Dharma, 1993)
There is in our day a deep disillusionment. Many people no longer believe that the endless growth of science will create a happier and more just world. There is a widespread distrust in technological progress, professionalized rationality, masculine, detached control, and the conquest of nature. We have seen how a political and technological bureaucracy can become the tool for the insanity of the Holocaust; how the endless production and consumption of gadgets coexists with a population vexed systemic injustice and violence; how a scientific establishment of unprecedented scope and power devotes itself to the creation of weapons of mass destruction; and perhaps most terrifyingly — how our entire civilization has developed forms of life that are toxic for us and for the natural world as a whole.